Impact of installation on the recovery of the bearing capacity of displacement piles in sensitive clay. Issue 1 (April 2021) - Yannie, Jorge; Karlsson, Mats; Dijkstra, Jelke
Abstract: Deep foundations are essential for the soft soil deposits that are ubiquitous in the Nordic countries. Precast driven displacement piles are commonly used, due to the ease of installation and their low cost. The stiffness and strength of the clay surrounding the piles will change during and after the pile installation process. This paper presents an effective stress based numerical framework that elaborates the pile set-up and pile ageing mechanisms observed empirically. For the trial case studied, it is demonstrated that the magnitude of the increase in axial bearing capacity over time is strongly linked to the pile installation stage. Furthermore, it is found that classic effective stress based soil mechanics concepts readily describe the observed behaviour.